L’expérience d’une double différence : quand l’autisme croise la diversité sexuelle et de genre - Maude Laflamme; Line Chamberland (Genre, Sexualité et Société)
The present article aims to synthesise existing knowledge regarding the reality of people who identify both as autistic and as members of the LGBTQ community. It features the results of a literature review on this topic, mainly conducted through a systematic keyword search within different multidisciplinary databases. Many of the collected writings establish cooccurrences between autism and gender or sexual minorities. Their authors move to explain these correlations by evoking three main theoretical proposals, which are either sociobiologically, psychologically or psychosociologically based. They also address difficulties experienced by autistic and LGBTQ people, in terms of discrimination, mental health and interactions with health professionals and peers, then express recommendations seeking to improve the global wellbeing of this particular community’s members.